Relationship Marketing Practices and Customer Loyalty: A Review with Reference to Banking Industry - Tawseef Ahmad Ganaie; Prof. Mushtaq Ahmad Bhat (International Journal of Engineering and Management Research, 2020)
Relationship marketing is seen as an effective weapon to retain the existing customers in order to reap the benefits of customer loyalty. With increase in competition, making customers loyal to firm is a challenging task particularly in banking sector where the products and services are homogenous and switching intentions among customers remain high. Researchers and practitioners are keen to understand the progression of research on the impact of relationship marketing practices on customer loyalty and financial performance. In view of the growing importance of relationship marketing and customer loyalty, present study attempts to review relationship marketing practices and customer loyalty and their linkages in the context of banking sector and to offer suggestions, on the basis of review of literature, to make bank customer relationships more effective and efficient.